The impact of pharmacist early active consultation (PEAC) on multidrug resistance organism treatment outcomes: A prospective historically controlled study - Du, Qian; Xi, Xin; Dong, Jie; Zhang, Tongyan; Li, Dongxuan; Dong, Yuzhu; Li, Wenjun; Huang, Guili; Zhu, Jun; Ran, Hailong; Gou, Jinghui; Chen, Cheng; et al. (Frontiers in Pharmacology, 2023)
Background & aim: Infectious disease (ID) consultation can improve multidrug-resistant organism (MDRO) treatment outcomes. However, the impact of clinical pharmacists' ID consultation on MDRO therapy, especially early initiation, has not been reported. In this study, we try to explore the impact of the pharmacist early active consultation (PEAC) on MDRO patient management. Methods: We conducted a prospective historical controlled study based on PEAC in MDRO patients. The retrospective control group was patients hospitalized 18 months before the PEAC initiation, and the prospective PEAC group was patients hospitalized 18 months after the PEAC initiation. Primary endpoint was 30-day all-cause mortality. Secondary outcomes were MDRO clinical outcome, duration of antibiotic use, length of stay, antibiotic consumption and antibiotic costs. Further subgroup analysis of secondary outcomes was performed by the condition at admission, MDRO pathogenicity and MDRO clinical outcome. Results: 188 MDRO patients were included. After adjusting for potential predictors, PEAC reduced the 30-day all-cause mortality by 70% (HR 0.30, 95%CI 0.09-0.96, P = 0.042). PEAC group had clinical improvement than control group (89.47% vs. 65.59%, P＜0.001), especially in patients with non-severe clinical conditions at admission (98.41% vs. 70.18%, P＜0.001). However, no significant differences were found between groups in length of stay, antibiotics consumption, and antibiotics costs. Conclusions: Early active pharmacy ID consultation can reduce 30-day all-cause mortality and improve clinical outcomes in MDRO patients.